Sun exposure inversely related to food sensitization during infancy. Issue 7 (11th August 2015) - Matsui, Teruaki; Tanaka, Kajiyo; Nakagawa, Tomoko; Sasaki, Kemal; Nakata, Joon; Sugiura, Shiro; Kando, Naoyuki; Ito, Komei
Abstract Background Autumn and winter birth (AWB) has been reported to be a risk factor for the development of food allergies. However, the association between seasonal factors and allergic sensitization during early infancy remains unclear. Methods We collected data from 732 patients regarding the total and specific immunoglobulin E (tIgE, sIgE) levels in infants younger than 6 months old from November 2001 to October 2012 from the institutional clinical database system. We then analyzed the relationship between the birth month and the value of each parameter. Furthermore, we identified any correlations between the number of sensitized patients and the monthly climatological parameters. Results The number of tIgE samples obtained from AWB patients (n = 482) was 2.1 times higher than that from patients born in the spring and summer (SSB, n = 225). The number of sIgE samples to egg white, cow's milk, and wheat, the sensitized ratio and the median sIgE titer were also all higher in AWB. The number of sensitized AWB patients to these allergens was 2.75, 3.05, and 3.97 times higher, respectively. A periodic change in the number of sensitized patients was observed annually (highest in October‐November and lowest in May). Among the climatological parameters examined, the average solar radiation during the 3‐month period after birth showed the strongest negative correlation with the number of sensitized patients (egg white: r = −0.976, cow's milk: r = −0.969, wheat: r = −0.975). Conclusions The amount of solar radiation immediately after birth had a strong negative correlation with allergen sensitization before 6 months of age.